2018
DOI: 10.9755/ejfa.2018.v30.i2.1602
|View full text |Cite
|
Sign up to set email alerts
|

Impact of production season on the chemical composition and health properties of goat milk and rennet cheese

Abstract: This study compared selected parameters of milk and rennet cheese produced from milk obtained from alpine goats during winter and summer feeding under climatic conditions of the Warmia and Mazury region. Milk from the winter season contained more protein, less vitamin A and over seven times less vitamin E than milk obtained in summer. In cheese from the winter season, the content of dry matter, fat, protein and vitamin A was lower when compared with cheese from the summer period. The content of total biogenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Polyunsaturated fatty acids are widely reported in milk, and their presence and differences may be due to seasonal variation of the anaerobic fungi population in the rumen (Koppova et al, 2008). Milewski et al (2018) reported that the fat from winter milk showed higher content of long-chained SFA and MUFA than the summer milk. The goatmilk fatty acid content is affected by variables such as dietary fat supplementation (Ayeb et al, 2015) and season (Czarniawska-Zajac et al, 2006).…”
Section: Composition Of Milk Fatty Acidsmentioning
confidence: 99%
See 2 more Smart Citations
“…Polyunsaturated fatty acids are widely reported in milk, and their presence and differences may be due to seasonal variation of the anaerobic fungi population in the rumen (Koppova et al, 2008). Milewski et al (2018) reported that the fat from winter milk showed higher content of long-chained SFA and MUFA than the summer milk. The goatmilk fatty acid content is affected by variables such as dietary fat supplementation (Ayeb et al, 2015) and season (Czarniawska-Zajac et al, 2006).…”
Section: Composition Of Milk Fatty Acidsmentioning
confidence: 99%
“…Branched FA concentrations were highly variable; C15:0 iso, C14:0 anteiso, and C16:0 anteiso were the most abundant constituents in the rainy season, but only C14:0 anteiso was significantly different. Milewski et al (2018) reported that summer milk had a higher proportion of PUFA n-6 and PUFA n-3 in the fat.…”
Section: Composition Of Milk Fatty Acidsmentioning
confidence: 99%
See 1 more Smart Citation